From Asia to Eurasia: China and India interests in Central Asia (International relations and international law Journal, 2018)
Central Asia, situating in the core of Eurasia and being a direct neighbor to China and extended neighbor to India attracts both countries in multiple aspects. With rich energy recourses and transit potential both India and China tries to play an active role in the region. While China enhances its engagement through regional initiatives as ‘Economic Silk Road’, India also wants to benefit and improve its involvement in regional cooperation. The security issue which is vital for both India and China formulate the sphere of interests of the region. The paper analyzes the main challenges of China- India-Central Asia cooperation and new opportunities to develop partnership.Key words: China-Central Asia relations, India-Central Asia relations, Central Asian cooperation.